How to lead academic departments successfully - Lindgreen, Adam; Irwin, Alan; Poulfelt, Flemming; Thomsen, Thyra Uth (How to guides, 2021)
"It is an old cliché that leading and managing academics is like herding cats. This book challenges this myth and presents a way to deal with the many challenges of academic leadership, from managing departments, research groups and teams to managing tensions between research and teaching. The book is a practical and stimulating guide to different pathways to successful academic leadership, both in personal and organizational terms. Including reflections and advice from experienced leaders, this book provides ideas and guidance to help current and aspiring leaders increase their own efficiency and effectiveness across the following areas: Dealing with conflict Engendering team spirit Ensuring diversity and inclusion Leading change in business schools Leading research groups Creating a triple crown business school Collaborating with other disciplines and practitioners. An experienced group of contributors reflects on their own successes and failures to shine new light on academic leadership to support your own sense of success as a practicing or aspiring departmental head. We also hope that this book will be instructive for those who simply want to understand how this crucial aspect of academic life operates"--